2012
DOI: 10.1068/p7281
|View full text |Cite
|
Sign up to set email alerts
|

Is Size Misperception of Targets Simply Justification for Poor Performance?

Abstract: Recent studies show that those who perform poorly on sporting activities involving targets recall the target as smaller than do better performers. Some have attributed the effect to action-specific perception, suggesting perception is influenced directly by how one interacts with an object. We proposed that underestimation of target size may instead serve as a justification for poor performance. We found that inaccurate dart throwers, given an excuse that the darts were of poor quality, were less likely to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 6 publications
2
23
1
Order By: Relevance
“…For example, the effect of dartthrowing performance on estimated size could occur because performance influences perceived size or because participants alter their judgments after missing the target to account for their poor performance. When participants were given an external reason for the poor performance (faulty darts), there was no need to justify performance, and in this case it was found that performance did not relate to estimate size (Wesp & Gasper, 2012).1 Although I admire the logic of this experiment, I hesitate to accept its results, because the dart-throwing paradigm does not appear to be particularly robust. Many of the reported "significant" findings have been only marginally significant (ps = .06, .001 and .02, and .05 in Canal-Bruland, Pijpers, & Oudejans, 2010;Wesp, Cichello, Gracia, & Davis, 2004; and Wesp & Gasper, 2012, respectively).…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…For example, the effect of dartthrowing performance on estimated size could occur because performance influences perceived size or because participants alter their judgments after missing the target to account for their poor performance. When participants were given an external reason for the poor performance (faulty darts), there was no need to justify performance, and in this case it was found that performance did not relate to estimate size (Wesp & Gasper, 2012).1 Although I admire the logic of this experiment, I hesitate to accept its results, because the dart-throwing paradigm does not appear to be particularly robust. Many of the reported "significant" findings have been only marginally significant (ps = .06, .001 and .02, and .05 in Canal-Bruland, Pijpers, & Oudejans, 2010;Wesp, Cichello, Gracia, & Davis, 2004; and Wesp & Gasper, 2012, respectively).…”
mentioning
confidence: 87%
“…Nevertheless, the logic offered by Wesp and Gasper (2012) and urged by Firestone and Scholl (in press-a) can be applied to the paddle effect. Participants were split into two groups, and each group was told a cover story that the task of blocking the ball would be either hard, because the ball would bounce at 1 Wesp and Gasper (2012) also suggested that the differences in distance estimates across participants who threw a heavy versus a light ball could have been due to a similar pattern of participants accounting for poor throwing performance by estimating that the distance was farther.…”
Section: Pitfall #2: Perception Versus Judgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, manipulating belief but not ability affects spatial judgments in just the way one would expect if demand explained the results. For example, falsely informing subjects that a recently ingested diet soda was in fact sugary decreases slant estimates (Williams, Ciborowski, & Durgin, 2012), telling subjects that a golf club once belonged to a famous golfer increases estimates of golf-hole size in a putting task (C. Lee, Linkenauger, Bakdash, Joy-Gaba, & Proffitt, 2011), and telling subjects that some darts to be thrown at a target are actually defective eliminates the correlation between throwing accuracy and size estimation (Wesp & Gasper, 2012). The demand account earns even further support from a more unlikely source.…”
mentioning
confidence: 99%